Avaliação de métodos de diagnóstico de vulvovaginites infecciosas em amostras cérvicos-vaginais coletadas no município de São Pedro/RN - Araújo, Valdiery Silva de (2020)
The vaginal microbiota, unlike the microbiota of most other parts of the body, is very dynamic and is characterized by occasional disturbances that can be influenced by age, sexual intercourse, personal hygiene, menses and hormone levels. It is estimated that vaginal infections alone account for over 10% of patient visits to the women's health care provider. Highlighting the most common causes of infectious vulvovaginitis are vulvovaginal candidiasis, bacterial vaginosis (BV) and trichomoniasis. The presumptive diagnosis of lower genital tract infections invariably leads to a significant number of women being misdiagnosed or ending up without an adequate diagnosis. This inaccuracy is also the cause of a significant number of women who are treated and labeled with a presumed infection who, in fact, are not infected with the suspected pathogens. In this perspective, the main objective of this work is to identify the most appropriate method for the diagnosis of the main infectious vulvovaginitis among three different techniques: GRAM staining, vaginal wet mount and the Papanicolaou test. For this, a cross-sectional descriptive study was carried out with the cervico-vaginal samples of 215 adult women from the city of São Pedro/RN. The results obtained from the examination of vaginal flow using direct microscopy methods (wet mount and GRAM staining) showed a prevalence of Candida spp. in 24.7% of the patients, 20% for BV and 1.9% for T. vaginalis. Among these women, 32.1% had no clinical complaints, while 5.1%, all of them. Burning (27.4%), itching (37.2%) and discharge (32.6%) have a higher prevalence when evaluated alone, than in association between them. Comparing the Pap test with the gold standard (direct microscopy), the sensitivity/specificity values of 58.5% / 95.1%, 69.8% / 97.7% and 75% / 99.1% were obtained for Candida spp., bacterial vaginosis and T. vaginalis respectively. Therefore, GRAM staining is evidenced as an eligible method in the diagnosis of vulvovaginitis. However, the Pap smear should not be ruled out due to its high specificity; consequently, the result when positive is useful. The findings of this work may support strategic public policies in the field of women's health, specifically early effective diagnosis of vulvovaginitis.